No Fixed Abode - Humphreys, R. author. aut Link
XIII, 222 p.
Keywords: Homelessness is now a much greater problem than twenty years ago. In Britain today around half-a-million homeless people form a regrettable permanent 'underclass'. This book spells out their similarities with the spurned vagrant of bygone days. It traces how for centuries emergent laws have combated alleged threats from unruly vagrants while largely ignoring causal factors like economic fluctuation, bad harvests, disease and war. It is argued that only educational and social reform will alleviate the homeless plight.